Satisfying Newcomers’ Needs: The Role of Socialization Tactics and Supervisor Autonomy Support - Chong, Jane; Beenen, G.; Gagné, Marylène; Dunlop, Patrick (SPRINGER, 2020)
© 2020, Springer Science+Business Media, LLC, part of Springer Nature.